The Effect of Coding Education with Minecraft EDU on Students' Problem Solving Skills and Their Attitudes towards Coding - Hanife Aktaş Kumral; Emre Çam (Uluslararası Türk Eğitim Bilimleri Dergisi)
In the current study, it was aimed to examine the effect of game-based Python coding education with Minecraft EDU on students' problem solving skills and attitudes towards coding. The study was designed with a one-group pretest-posttest experimental model, which is one of the quantitative research methods supported by qualitative data. The research group consists of 7th grade students studying in a public school in Zile district of Tokat province in the 2021-2022 academic year. The study was maintained with a 6-week program of 12 hours in total. The data collection tools used to collect data within the scope of the research are "Problem Solving Inventory for Children (PSI)", "Attitude towards Coding Scale" and semi-structured interview form. According to the findings, no difference was found in the problem solving skills of the students participating in the study. Gender, daily game playing time and daily internet usage time variables were found to have no effect on problem solving skills. However, the variables of computer use duration show a significant difference. As a result of the research, no difference was found in students' attitudes towards coding. Similarly, it was found that gender, duration of computer use (years), daily computer use, daily internet use and daily computer game playing time had no effect on attitudes towards coding. In addition, it was determined that game-based coding education is fun, more instructive, provides active learning, increases interest and motivation towards the lesson and makes the process more instructive and the learning process enjoyable. Moreover, it was determined that text-based coding caused difficulties for the students and the fact that the code groups were in English made the process more difficult.